A qualitative research on reproductive concerns of the patients with Peutz-Jeghers syndrome - Mengxia Pan; Beilei Ye; Huajuan Shen; Jiyong Jin; Qiong Zhang (Journal of Psychosomatic Obstetrics and Gynecology)
Objectives To gain a deeper understanding of the real experiences and needs of the patients of Peutz-Jeghers syndrome (PJS) with fertility concerns.Design A qualitative study.Methods Phenomenological research and Semi-structured method were conducted with the patients of PJS (N = 16), and the interview data were analyzed using inductive content analysis strategies.Results 16 patients were interviewed, including 13 women and 3 men partners. We identified 5 themes, including: (i) Heritability of disease, (ii) Potential risks of reproduction; (iii) The difficulties in raising children; (iv) family and social support. (V) Need support from multiple sources.Conclusion The findings of this study demonstrate that patients with Peutz-Jeghers syndrome (PJS) who are of childbearing age experience various reproductive concerns and other manifestations. Therefore, it is essential to offer individualized psychological interventions for PJS patients at different psychological stages, with the support of healthcare professionals, family, and social networks.